Effect sizes as result interpretation aids in single‐subject experimental research: description and application of four nonoverlap methods. (10th February 2015) - Rakap, Salih
<x xml:space="preserve">Abstract</x> Single‐subject experimental research (SSER), one of the most commonly used research methods in special education and applied behaviour analysis, is a scientific, rigorous and valid method to evaluate the effectiveness of behavioural, educational and psychological treatments. However, studies using single‐subject experimental research designs are often excluded from meta‐analyses of evidence‐based practices due to the lack of methodological consensus on the type of effect size indices to be used to determine treatment effect. To promote the use of effect size indices as an adjunct to visual analysis, this article describes four nonoverlap methods (PND, IRD, PEM‐T and Tau‐U) and demonstrates their application to data obtained from studies employing different SSER designs. Advantages and disadvantages of each method are highlighted and considerations for selecting the most appropriate method are provided for researchers and practitioners.